The outline of Levas Vladimirovas' professional career - Raguotienė, Genovaitė (Knygotyra, 1988)
Levas Vladimirovas, born on February 27, 1912, is an outstanding authority in the field of modern Soviet library science, as well as the history of books and libraries.The essential part of Levas Vladimirovas' life and his entire scientific and teaching career is closely linked with Vilnius University. After World War II, he lectured on Marxism-Leninism (1948), the history of the book, and library science (1951). He was the first head of the Department of Library Science (1952-1964) and later the Department of Library and Information Science (1970-1973). Since 1973, Levas Vladimirovas has been the head of the Department of Information Science. Additionally, between the years 1948-1964, he served as the director of the university library.Between 1964-1970, Levas Vladimirovas was elected director of the UNO Dag Hammarskjöld Library. His contribution to the development of the library is immense. Levas Vladimirovas was also a member of various international library organizations and institutions.Alongside his many-sided teaching, library, and social activities, Levas Vladimirovas has made significant contributions to science. More than 300 publications in Lithuanian, Russian, English, and other languages are attributed to his pen. The focus of Levas Vladimirovas' research lies in the history of Lithuanian books, libraries, and culture during the feudal and capitalist periods. He was the first to investigate both known and new phenomena in the Lithuanian cultural heritage through the lens of Marxist methodology.Among his most outstanding works are Essays on the History of the Book and Libraries in Lithuania (XV cent. to 1917) ("Lietuvos bibliotekų ir knygos istorijos bruožai (XV a.-1917 m.)", 1965); publications dedicated to the pioneers of book printing in Vilnius—F. Skorina and I. Fedorov; and works on the history of Vilnius University and its library. L. Vladimirovas' comprehensive work The History of the Book ("Knygos istorija", 1979) provides a broad panorama of world book history, starting with primitive scripts up to the 17th century.In 1962, for his teaching, scientific, and social activities, Levas Vladimirovas was awarded the title of Honored Art Worker of the Lithuanian SSR. The professor was also among those who were awarded the Lithuanian State Prize for The History of Vilnius University ("Vilniaus universiteto istorija") in three volumes.
Keywords: -